Agresivitas pada remaja anggota perguruan pencak silat: menguji peranan konformitas - Mokhamad Arif Widiyanto; Dr. IGAA Noviekayati, MSi., Psikolog; Amherstia Pasca Rina, M.Psi., Psikolog (INNER: Journal of Psychological Research, 2023)
Adolescence is a transitional phase from childhood to adulthood, in this stage adolescents experience psychological, physical, and psychosocial changes, in the stage of human development the adolescent phase must be passed. One of the phases that are looking for identity is joining a silat school group. This study aims to determine the relationship between conformity behavior and the aggressiveness of adolescent members of silat college groups in the Mojokerto area. The method used in this study is quantitative by using validity and reliability tests for data testing, while for analysis of research results using the normality test, linearity test, and Product Moment Correlation test. The results of this study indicate that the normality test is a normal distribution because the data spread on a diagonal line and follows the diagonal line or the histogram graph. The linearity test produces a significant value of 0.000 which means that there is a relationship between conformity behavior and the aggressiveness of adolescent members of the silat school group in the Mojokerto area. Subsequent tests were carried out using the Product moment correlation to obtain a correlation coefficient of -0.563 and a significance of p = 0.000. This means that there is a significant negative relationship. This means that the higher the conformity of young members of the Silat College in the Mojokerto area, the lower the aggressiveness of the young members of the Silat college in the Mojokerto area.